Massive loculated pleural effusion in a patient with pancreatic pseudocyst due to alcohol-related chronic pancreatitis. (9th April 2014) - Lam, Stephen; Banim, Paul
Abstract : A 47-year-old man with a history of alcohol-related pancreatitis was admitted with dyspnoea due to a moderate right-sided pleural effusion. Diagnostic pleural tap showed an amylase of 6078 U/L. CT demonstrated a pancreatic pseudocyst with communication to the pleural cavity. Conservative medical management and chest drainage were started, but after 13 days the patient became acutely unwell with severe dyspnoea and worsening chest pain. Chest X-ray and subsequent CT demonstrated a massive pleural effusion with mediastinal shift. Ultrasound scan demonstrated loculation of the effusion requiring insertion of a large bore chest drain to relieve symptoms. He was transferred to a pancreaticobiliary centre, but subsequently made a good recovery without the need for a further procedure. This case highlights massive pleural effusion with subsequent loculation as a rare complication of chronic pancreatitis.